Past, present and future using silicone breast implants in Brazil, a 45-year report - Antonio Roberto Bozola (Revista Brasileira de Cirurgia Plástica)
The author lived with breast implants and tells the story of evolution in his 45 years of experience. It points out the main points of this evolution, the coincidences, and complications over time, and proposes possible future events in the end.